Aesthetic Outcomes of Perineal Reconstruction with the Lotus Petal Flap. Issue 6 (June 2021) - Hellinga, Joke; Fleer, Joke; van der Lei, Berend; Werker, Paul M.N.; van Etten, Boudewijn; Stenekes, Martin W.
Abstract : Background: The lotus petal flap can be applied for reconstruction of extensive defects in the vulvoperineal area. Studies on aesthetic outcomes are lacking. This study aimed to fill this gap. Methods: All patients who underwent lotus petal flap reconstruction between October 2011 and December 2015 were asked permission to have their photographs used. Two questionnaires were used: (1) the Strasser score to assess the overall aesthetic results (range 0–15) and (2) the Patient and Observer Scar Assessment Scale (POSAS; range 6–60). Six plastic surgeons and 6 laymen filled in the Strasser score and the Observer scale of the POSAS. Patients filled in the Strasser score, the Patient scale of the POSAS and scored their overall satisfaction with the aesthetic results on a Likert scale (0–10). Results: The photographs of 11 patients were included. The median Strasser score of all observers of 11.9 (range 0.0–75.0) indicated a mediocre aesthetic result. The median total POSAS score of 15.6 (range 6.0–41.0) indicated an aesthetically acceptable scar. Strasser and POSAS scores of the plastic surgeons and laymen did not differ significantly from the patients' scores. The patient satisfaction score with the aesthetic result was a median of 6.0 of 10. Conclusions: The findings indicate that, overall, patients were moderately satisfied with the aesthetic results of their lotus petal flap reconstructions, as were the plastic surgeons and laymen. For clinical practice, it is important that the plastic surgeon manages expectations carefully before surgery, as it is possible that patients might experience a rather low aesthetic outcome after perineal reconstruction.